THE BEHAVIOR OF THE EXISTENCE OF THE FOREST IN THE HARAU SUB DISTRICT REGENCY HARAU DISTRICT LIMA PULUH KOTA REGION - Friska Safitri, Dela; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Farida, Farida (Pendidikan Geografi, 2014)
ABSTRACT This research aimed to obtain, analyze and discuss the data the behavior of the public about the existence of the forest in Harau Regency Harau District Lima puluh Kota Region views of : 1 ) the destruction of forests , 2 ) preservation of forests and 3 ) forest turned into fields. This type of research is classified as descriptive. Population was all the heads of families residing in Harau regency totaling 761 households. Samples were taken in two ways, sample areas were taken by purposive sampling technique, taking Jorong Harau due to close and surrounded by forests, sample respondents drawn with proportional random sampling technique with a proportion of 25 % , so that the respondent amounted to 82 households. Collecting data using guided inquiry, statistical analysis used was descriptive using percentage formula.The results showed as follows: 1 ) the behavior of the public about the destruction of forests in Harau Regency Harau District Lima puluh Kota Region average score was 2.45 with 61,2 % of respondents achievement levels that are in fairly good criteria, (2) peoples behavior about forest conservation in in Harau Regency Harau District Lima puluh Kota Region average score was 1,97 with 49,1% of respondents achievement levels that are less well on the criteria and (3) the behavior of the public the forest turned into fields in Harau Regency Harau District Lima puluh Kota Region average score was 1,71 with 40,4% of respondents rate the performance criteria are not good